Prevention of Hypertension at Home - Aris Widiyanto; Santy Irene Putri; Asruria Sani Fajriah; Joko Tri Atmojo (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Hypertension is a systolic blood pressure (SBP) value of 130mmHg or more and / or a diastolic blood pressure (DBP) of more than 80 mmHg. One of the factors in the development of essential hypertension is the patient's genetic ability to respond to salt. Various non-pharmacological interventions have been shown to be effective in lowering blood pressure and preventing hypertension. The most effective interventions are weight loss, reduced Na + intake, increased potassium intake, increased physical activity, reduced alcohol consumption and a diet such as Diet Approaches to Stop Hypertension (DASH) which combines several elements that are useful in controlling blood pressure. A diet that emphasized fruit and vegetable intake significantly reduced high blood pressure during the 8-week intervention. Some things we can do to help reduce hypertension at home are to maintain a diet and daily lifestyle and can be done through hydrotherapy (soaking your feet in warm water).